2021
DOI: 10.1038/s41389-021-00302-5
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-mediated transition of resident fibroblasts to cancer-associated fibroblasts promotes cancer metastasis in gastrointestinal stromal tumor

Abstract: Cancer-associated fibroblasts (CAFs) are the most abundant cells in the tumor microenvironment. Crosstalk between tumor cells and CAFs contributes to tumor survival in most epithelial cancers. Recently, utilizing gastrointestinal stromal tumor (GIST) as a model for sarcomas, we identified paracrine networks by which CAFs promote tumor progression and metastasis. However, the mechanisms by which CAFs arise in sarcomas remain unclear. Here, RNA sequencing analysis revealed that transforming growth factor-β1 (TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…CAFs can be derived from normal resident tissue fibroblasts that are activated by adjacent tumor cells. A majority of stromal activated fibroblasts initially originate from local resident fibroblasts, which respond to TGFb and undergo myofibroblastic differentiation during tissue wound healing and cancer progression (7)(8)(9). Bone marrow-derived mesenchymal stem cells (MSCs) are a source of CAFs via recruitment by tumor cell secreted factors.…”
Section: Diversity Of Caf Originmentioning
confidence: 99%
“…CAFs can be derived from normal resident tissue fibroblasts that are activated by adjacent tumor cells. A majority of stromal activated fibroblasts initially originate from local resident fibroblasts, which respond to TGFb and undergo myofibroblastic differentiation during tissue wound healing and cancer progression (7)(8)(9). Bone marrow-derived mesenchymal stem cells (MSCs) are a source of CAFs via recruitment by tumor cell secreted factors.…”
Section: Diversity Of Caf Originmentioning
confidence: 99%
“…In Tgfbr2 KO tumors there was an increase of various collagen-coding genes, including Col1a1, Col6a1, and Col6a2 ( Figure 5D and 5E ), consistent with the presence of a fibro-mucinous stroma ( Figure 3H and Figure 3I ). Unexpectedly, many of the genes upregulated in the Tgfbr2-targeted tumors were indicative of increased TGFβ signaling, including Tnc, Timp1, and Arg1, which are induced by TGFβ (Calon et al, 2012; Kwak et al, 2006; Mondanelli et al, 2017; Yoon et al, 2021) ( Figure 5E ). There was also downregulation of Sftpb, which is negatively regulated by TGFβ (Wesselkamper et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, multiple studies have shown that CAFs crosstalk with cancer cells via secreting various cytokines and chemokines [46,47] , and other studies have demonstrated that metabolic reprogramming of CAFs are important in cancer progress [48] . For example, TGF-β1 secreted by CAFs is associated with gastrointestinal stromal tumor migration and metastasis [49] . Moreover, lactate secreted from CAFs could be absorbed by prostate cancer cells and promote their growth [50] .…”
Section: Discussionmentioning
confidence: 99%